"Literarna kritika ni upravičena, če je na kocki krik milijonov src" - Andringa, Els (Primerjalna književnost, 2010)
After Hitler came to power in Germany and the books of rejected writers were burned in 1933, many writers, publishers, and critics fled. The Netherlands became a center of exile literature because two of the biggest publishers wereestablished in Amsterdam. How did this exile literature affect existing Dutch literary field? Did it achieve a lasting place in Dutch literary history? This paper examines how the reactions in the press reflected positions and changes in the established Dutch literary field. It also addresses the question why exile literature, even if it was closely connected with Dutch history, almost completely disappeared from sight.
Keywords: literatura v eksilu; svetovna vojna 1939-1945; nemška književnost; German-language literature; Nizozemska; literarna recepcija